2014
DOI: 10.1007/s10681-014-1239-5
|View full text |Cite
|
Sign up to set email alerts
|

Root and physiological characteristics associated with drought tolerance in Iranian tall fescue

Abstract: Research on crop response to deficit irrigation is important to reduce agricultural water use in areas where water is a limited resource. The objective of this study was to evaluate changes in physiological and root traits under mild and intense drought stress in tall fescue. It also sought to find associations between these changes and field drought tolerance. A total of 24 tall fescue genotypes were selected from a wide polycross population and assessed for field drought tolerance during 2011-2012 in the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 53 publications
5
49
0
Order By: Relevance
“…Decreased or increased carotenoid levels under water stress have been reported in several species (Ebrahimiyan et al, 2013;Irani et al, 2015). The accumulation of compatible solutes such as proline and WSC is a common adaptation mechanism acquired by annual and perennial grasses under water stress (Volaire and Lelièvre, 1997;Bajji et al, 2001;Pirnajmedin et al, 2015). The accumulation of compatible solutes such as proline and WSC is a common adaptation mechanism acquired by annual and perennial grasses under water stress (Volaire and Lelièvre, 1997;Bajji et al, 2001;Pirnajmedin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Decreased or increased carotenoid levels under water stress have been reported in several species (Ebrahimiyan et al, 2013;Irani et al, 2015). The accumulation of compatible solutes such as proline and WSC is a common adaptation mechanism acquired by annual and perennial grasses under water stress (Volaire and Lelièvre, 1997;Bajji et al, 2001;Pirnajmedin et al, 2015). The accumulation of compatible solutes such as proline and WSC is a common adaptation mechanism acquired by annual and perennial grasses under water stress (Volaire and Lelièvre, 1997;Bajji et al, 2001;Pirnajmedin et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In a glasshouse study evaluating the morphological and physiological responses of three grasses (perennial ryegrass, cocksfoot and tall fescue) to varied moisture availability, Turner et al [67] concluded that tall fescue appeared to have the greatest scope for persistence under moisture stress because its dry matter was less affected and it was able to recover more quickly following rewatering. Tall fescue accessions also differ with regard to tolerance of summer drought [68,69] conditions because their deep tap root allows them to access water at depth [49,58]; however, there has been some concern about their long-term persistence [12]. These species may also be worth evaluating under restricted irrigation conditions and may perform better than red clover.…”
Section: Perennial Foragesmentioning
confidence: 99%
“…In a glasshouse study evaluating the morphological and physiological responses of three grasses (perennial ryegrass, cocksfoot and tall fescue) to varied moisture availability, Turner et al [67] concluded that tall fescue appeared to have the greatest scope for persistence under moisture stress because its dry matter was less affected and it was able to recover more quickly following re-watering. Tall fescue accessions also differ with regard to tolerance of summer drought [68,69] suggesting that there may be opportunities to select and grow more adapted varieties under moisture stress conditions. Phalaris (Phalaris aquatica L.) is another temperate perennial grasses species that has deep roots and is generally more tolerant to drier conditions than perennial ryegrass.…”
Section: Perennial Foragesmentioning
confidence: 99%
“…Drought tolerance mechanisms often include the development of expanded or deep root systems and other physiological functions such as reduce transpiration, osmoregulation and oxidative stress protection (Pirnajmedin et al., ). In this study, three peanut genotypes had differential responses to pre‐flowering drought for root and other physiological traits.…”
Section: Discussionmentioning
confidence: 99%
“…(), Krishnamurthy et al. () and Pirnajmedin, Majidi, and Gheysari (). The size and function of root systems have been studied by Nardini, Salleo, and Tyree (), Sperry, Stiller, and Hacke (), Songsri et al.…”
Section: Introductionmentioning
confidence: 99%